The governance of China's foreign aid system: Evolution and path dependence. (31st October 2019) - Zhao, Jianzhi; Jing, Yijia
Summary: As China become a major donor in international development, there is an urgent need to improve its capacity to govern its aid policy and management system. This study provides a comprehensive review of China's aid governance system and its evolution along the time, showing its changes and nonchanges. Path dependence effects are used to explain such evolution and are further illustrated by the consistent central role of the Ministry of Commerce in the aid system and by the central–provincial arrangement of development finance. Further, by exploiting limited yet novel evidence of the newly established State International Development Cooperation Agency, we argue that path dependence effects make it difficult to achieve the goal to comprehensively restructure the aid governance system by establishing State International Development Cooperation Agency. The study offers a useful perspective to understand the functioning and future evolution of China's aid governance system.